Analisis Strategi Pendayagunaan Aset Wakaf Pada Persyarikatan Muhammadiyah - Rohman, Bahrul (Jurnal Ilmiah Ekonomi Islam, 2023)
This study presents the utilization strategy of waqf assets in the Muhammadiyah Association, Muhammadiyah Association is a non-profit organization engaged in various fields including social, religious, education and others. Waqf assets managed by Muhammadiyah become a huge potential so that strategies are needed waqf in Muhammadiyah can be optimized to the maximum. The purpose of this research is to prioritize the strategies proposed by waqf experts for Muhammadiyah. The method used in this research is a qualitative method with a Strengths, Weaknesses, Opportunities and Threat (SWOT), analysis approach with an analytical tool using the Analytic Network Process method to provide a classification of alternatives given by waqf experts. In this method, the strength factor, namely waqf assets Sabang to Merauke, is more dominant than the presence of supporting regulations, from the weakness factor it is found that limited human resources have the most influence on Muhammadiyah's weaknesses. Meanwhile, from the opportunity factor, the ability of the nazir to get results is more dominant, and Muhammadiyah's biggest threat is the number of waqf assets in private names. So that the main strategy carried out is to maximize opportunities, namely increasing the professionalism of Nazir.